Arthroscopic therapy of rotator cuff diseases: A bibliometric study of the past 2 decades (2002–2021) - Jin, Hongfu; Ding, Yilan; Wang, Weiyang; Ye, Ruixi; He, Miao; Xie, Wenqing; Li, Hengzhen; Xiao, Wenfeng; Li, Yusheng (Frontiers in Surgery, 2022)
Purpose: Rotator cuff diseases, as a common cause of shoulder pain and disability, have seriously affected the patients’ daily life. Rotator cuff repair techniques have been a hot topic in the arthroscopic therapy field. Our study was to use bibliometrics analysis to clarify the current status and research trends in the field of arthroscopic therapy of rotator cuff diseases. Methods: The publications relating to arthroscopic therapy of rotator cuff diseases published from 2001 to 2021 were obtained from the Web of Science Core Collection (WoSCC) database. The R software and VOSviewer software were used for the cross-sectional bibliometric and scientometric analysis. Results: A total of 4567 publications about arthroscopic therapy of rotator cuff diseases published between 2002 and 2021 retrieved from the WoSCC database were analyzed in our study. The results showed that the USA made the largest contribution to this field. The most relevant institutions were Seoul National University, Rush University, and Hospital for Special Surgery. Stephen S Burkhart was the most relevant researcher in this field with the largest number of publications, as well as the highest H-index and G-index. The journal ARTHROSCOPY contributed the largest number of publications in the past 2 decades. Considering the H-index and G-index, ARTHROSCOPY was also the journal with the largest impact in this field. Conclusions: Arthroscopic Therapy of Rotator Cuff Diseases Related research presented a rising trend in the past 2 decades. The USA can be regarded as the leader because of its huge contributions to this field. The journal ARTHROSCOPY published the largest number of publications in this field. It can be predicted that research about advanced arthroscopic techniques and postoperative pain management of patients with rotator cuff diseases will be the next research hotspots in the following years.